Mapping the Local Wisdom of Sasi Laut Culture in Nuwewang Village, Maluku Province - Heinrich Rakuasa (Geographica: Science and Education Journal, 2022)
Local wisdom is an effort and resilience of the community to manage and preserve its natural products by relying on certain customary rules. Since the 16th century, natural resources in maluku have been managed with a system called sasi. Sasi as a form of communal resource management practice carried out for generations in various locations in Maluku and parts of West Papua, this practice has long been believed to be one of the traditional wisdoms that is efficient in maintaining resource sustainability. This research focuses more on mapping the sea chassis area in Nuwewang Village, the sea chassis itself is a traditional open and close system for the utilization of certain marine resources that applies in a downward manner. This study aims to map local wisdom in the form of sea chassis applied in Nuwewang Village. The methods used are surveys and interviews, with data analysis carried out spatially using remote sensing methods based on geographic information systems. The results showed that the types of marine life that were breastfed were Sea Cucumbers (Holothuroidea spp) and Lola Snails (Trochus niloticus) as well as the boundary of the sea chassis from the eastern part starting from Tanjung Ayam to Tanjung Garam in the west with a coastline length of 13.34 km. The total area of sea chassis area in Nuwewang Village is 514.12 Ha